Effect of sodium-glucose cotransporter 2 (SGLT2) inhibitors on left ventricular remodelling and longitudinal strain: a prospective observational study - Sergio Gamaza-Chulián; Enrique Díaz-Retamino; Fátima González-Testón; José Carlos Gaitero; María José Castillo; Raquel Alfaro; Elías Rodríguez; Eva González-Caballero; Antonio Martín-Santana (BMC Cardiovascular Disorders, 2021)
Abstract Background Sodium-glucose cotransporter 2 inhibitors (SGLT2i) lower cardiovascular events in type 2 diabetes mellitus (T2DM) patients, although the mechanisms underlying these benefits are not clearly understood. Our aim was to study the effects of SGLT2i on left ventricular remodelling and longitudinal strain. Methods Between November 2019 and April 2020, we included 52 patients with T2DM ≥ 18 years old, with HbA1c between 6.5 and 10.0%, and estimated glomerular filtration ≥ 45 ml/min/1.73 m2. Patients were classified into SGLT2i group and control group, according to prescribed treatment by their referring physician. Conventional and speckle tracking echocardiography were performed by blinded sonographers, at baseline and after 6 months of treatment. Results Among the 52 included patients (44% females, mean age 66.8 ± 8.6 years, mean HbA1c was 7.40 ± 0.7%), 30 patients were prescribed SGLT2i and 22 patients were classified as control group. Mean change in indexed left ventricular mass (LVM) was − 0.85 ± 3.31 g/m2 (p = 0.003) in the SGLT2i group, and + 2.34 ± 4.13 g/m2 (p = 0.58) in the control group. Absolute value of Global Longitudinal Strain (GLS) increased by a mean of 1.29 ± 0.47 (p = 0.011) in the SGLT2i group, and 0.40 ± 0.62 (p = 0.34) in the control group. We did not find correlations between changes in LVM and GLS, and other variables like change in HbA1c. Conclusions Among patients with T2DM, SGLT2i were associated with a significant reduction in indexed LVM and a significant increment in longitudinal strain measured by speckle tracking echocardiography, which may explain in part the clinical benefits found in clinical trials.